Multi-physics modelling and performance analysis of an air-core reactor in the framework of solid-state fault current limiters - Akin, Firat; Arikan, Oktay; Kucukaydin, Baris (ELSEVIER SCIENCE SA, 2024)
This study presents a comprehensive multi-physics modelling of an air-core reactor operating within a solid -state fault current limiter. By utilizing an air-core reactor in the solid -state fault current limiter, it is aimed to avoid magnetic saturation and assess a conventional fault current limiting device within a contemporary fault current limiter topology. Within the employed fault current limiter topology, the air-core reactor not only limits fault current during grid faults but also carries nearly the entire network current under normal operational conditions. Therefore, the performance of air-core reactor is investigated through thermal, electromagnetic and electrostatic aspects for normal and fault conditions. A 380 V test prototype is employed to validate the coupling of reactor model and electric circuit dynamics in the simulations. Furthermore, current results of high voltage simulations are supported by PSCAD results to reveal the results accuracy. During the operation of air-core reactor in normal and fault cases, the distribution of heat originating from eddy and resistive losses was examined through convection, radiation and conduction mechanisms. Moreover, the electric field intensities affecting the reactor are obtained for different operating conditions through electrostatic analysis, whereas the electromagnetic analysis reveals the magnetic flux densities and magnetic forces acting on the reactor.
Keywords: Finite element method; Solid -state fault current limiter; Air-core reactor; Thermal analysis; Electric field analysis; Electromagnetic analysis; Engineering